Classical Literature: A Very Short Introduction - Allan, William (New York Oxford University Press, 2014)
William Allan's Very Short Introduction provides a concise and lively guide to the major authors, genres, and periods of classical literature. Drawing upon a wealth of material, he reveals just what makes the 'classics' such masterpieces and why they continue to influence and fascinate today.
Includes Index and Illustrations.
Keywords: Classical literature -- History and criticism